Nutrient composition of mealtimes and its association with the energy intake of subsequent meals among Mexican adults. (1st September 2021) - Sánchez-Pimienta, Tania G.; Quezada-Sánchez, Amado D.; Rivera, Juan A.; Shamah, Teresa; Batis, Carolina
Abstract: The composition of the diet influences energy intake by affecting satiety. Macronutrients have a hierarchical effect on satiety, where proteins have the greatest influence, followed by carbohydrates and fats. Alcohol consumption has also shown an effect on increasing energy intake in subsequent meals. Most of this evidence comes from studies under controlled conditions but, it is not clear if effects of diet composition are maintained or counteracted by other determinants of EI in real life. In this paper, we described the diet composition by mealtime in a sample of free-living Mexican adults, as well as evaluated its association with the energy intake in subsequent meals between- and within-subjects. We used information from a national cross-sectional survey of the urban Mexican population. Dietary information was collected by an automated multiple-pass 24-h recall and all participants had information from three non-consecutive days (two weekdays and one weekend). We analyzed information from adults from 20 years and older and used mixed-effects hybrid models that isolate the intra-subject, from the between-subject associations using a substitution approach. We found that alcohol and added sugars were associated with an increased EI between- and within-subjects, while fiber was associated with a decreased EI in subsequent meals within-subjects. Between-subjects, the higher intake of proteins was associated with a decrease in EI, whereas carbohydrates were associated with an increased EI in subsequent meals. We concluded that the composition of the diet at one mealtime predicted EI in subsequent meals of free-living subjects. Understanding the effects of diet composition could guide strategies to reduce EI and obesity prevention.